International Refugees in The Protection of Human Rights: A Discourse of International Humanitarian Law and Human Rights Law - Supriyadi, Slamet (International Law Discourse in Southeast Asia, 2022)
Refugees are defined as people who are due to a reasonable fear of persecution, caused by reasons of race, religion, nationality, membership in certain social groups and political parties, are outside their nationality and do not want protection from the country. When refugees leave their home country or residence, they leave their lives, homes, possessions and family. The refugees cannot be protected by their home country because they are forced to leave their country. Therefore, protection and assistance to them is the responsibility of the international community. In countries receiving refugees, they often experience inhumane treatment such as rape, assault, discrimination, repatriated by force, those lead to the violation of human rights. There has been regulation for human rights in refugee issues both internationally and regionally, for instance Convention related to Status of Refugee 1951 and The Protocol related to the Status of Refugee 1967. There are at least five basic rights of refugees, they are the right to be protected from returning to the country of origin forcibly (non refoulement), the right to seek asylum, the right to obtain equality and non-discrimination, the right to live and to be secured, as well as the right to return home.